Excessive N and K fertilizers effect on growth and disease severity of basal stem rot of oil palm seedlings grown on peat soil - Md Arif, Abdullah Wafi (2015)
Oil palm (Elaeis guineensis Jacq.) is a main plantation crop in Malaysia. Basal stem rot disease (BSR) is one of the most serious disease that cause major losses in the oil palm plantation in South East Asia, especially in Malaysia and Indonesia. Basal stem rot is caused by white fungus called Ganoderma. Several species of Ganoderma have been reported and Ganoderma boninense is a well-known pathogen to oil palm. Oil palm is a high nutrient demanding crop. Application of N and K nutrients may promote growth and decrease disease severity. Therefore, the objectives of this study were to examine the effect of excessive N and K on growth and disease severity of oil palm seedlings grown on peat soil. The experiment was carried out in shade house at Ladang 2, Universiti Putra Malaysia. Three treatments and five replications with seven oil palm seedlings for each replication were used. The treatments were N and K optimum, N and K excessive and control treatment (NPK blue). For each treatment, half of oil palm seedlings were inoculated with Ganoderma boninense, whiles the other half was without Ganoderma. The experiment was arranged in randomized complete block design (RCBD). The parameters measured were total frond numbers, bole diameter, seedlings height, chlorophyll contents and basal stem rot disease severity by disease severity index of foliar (DSIF). The result showed difference patterns of growth for every treatment from June until November (six month). Overall result showed that excessive N and K fertilizer gave an adverse effect on oil palm seedlings growth. Moreover, disease severity index of foliar result also showed that excessive N and K fertilizer have a high disease severity compared to other fertilizer treatments.